(untitled) (Hoboken, N.J., 2006)
Identification of Microorganisms by Mass Spectrometry represents the most comprehensive and up-to-date work on the topic currently available. It is liberally illustrated with figures and tables and covers every aspect of spectrometric identification of microorganisms, including experimental procedures, various means of sample preparation, data analysis, and interpretation of complex mass spectral data.
Keywords: Microorganisms,Mass spectrometry,Bacteriological techniques,Spectrum analysis,Vi sinh vật,Phép đo phổ khối lượng,Kỹ thuật vi khuẩn học,Phân tích quang phổ; Identification,Methods,Methods,Nhận dạng,Phương pháp,Phương pháp